A Novel Situational Awareness Scoring System in Pediatric Cardiac Intensive Care Unit Patients - Baloglu, Orkun; Kormos, Kristopher; Worley, Sarah; Latifi, Samir Q. (Journal of Pediatric Intensive Care, 2022)
The aim of this study was to describe the performance of a novel Situational Awareness Scoring System (SASS) in discriminating between patients who had cardiac arrest (CA), and those who did not, in a pediatric cardiac intensive care unit (PCICU). This is a retrospective, observational-cohort study in a quaternary-care PCICU. Patients who had CA in the PCICU between January 2014 and December 2018, and patients admitted to the PCICU in 2018 who did not have CA were included. Patients with do not resuscitate or do not intubate orders, extracorporeal membrane oxygenation, ventricular assist device, and PCICU stay < 2 hours were excluded. SASS score statistics were calculated within 2-, 4-, 6-, and 8-hour time intervals counting backward from the time of CA, or end of PCICU stay in patients who did not have CA. Cross-validated discrete time logistic regression models were used to calculate area under the receiver operating characteristic (AUC) curves. Odds ratios (ORs) for CA were calculated per unit increase of the SASS score. Twenty-eight CA events were analyzed in 462 PCICU admissions from 267 patients. Maximum SASS score within 4-hour time interval before CA achieved the highest AUC of 0.91 (95% confidence interval [CI]: 0.86–0.96) compared with maximum SASS score within 2-, 6-, and 8-hour time intervals before CA of 0.88 (0.79–96), 0.90 (0.85–0.95), and 0.89 (0.83–0.95), respectively. A cutoff value of 60 for maximum SASS score within 4-hour time interval before CA resulted in 82.1 and 83.2% of sensitivity and specificity, respectively. OR for CA was 1.32 (95% CI: 1.26–1.39) for every 10 units increase in the maximum SASS score within each 4-hour time interval before CA. The maximum SASS score within various time intervals before CA achieved promising performance in discriminating patients regarding occurrence of CA.
Keywords: severity of illness; cardiac arrest; electronic health record; critical illness; pediatric